Chemokine transport dynamics and emerging recognition of their role in immune function. (March 2018) - Moore, James E.; Brook, Bindi S.; Nibbs, Robert J.B.
Abstract: Leukocyte migration is critically important during all protective and pathological immune and inflammatory responses. Chemokines play fundamental roles in this process, and chemokine concentration gradients stimulate the directional migration of leukocytes. The formation and regulation of these gradients is poorly understood. These are complex processes that depend on the specific properties of each chemokine and interactions between physical, biological and biochemical processes, including production, diffusion, advection, scavenging, post-translational modification, and extracellular matrix (ECM) binding. While some of these mechanisms have been investigated in isolation or limited combinations, more integrative research is required to provide a quantitative knowledge base that explains how chemokine gradients are established and maintained, and how cells respond to, and modify, these gradients. Highlights: Chemokine concentration gradients stimulate directional leukocyte migration. Multiple physical and biological factors shape chemokine gradients. Integrating these factors provides new insights into gradient form and function.